Exxentric Strength Row. investigating the usefulness of an add-on product for flywheel-based strength training - Henriksson, J. (KTH Royal Institute of Technology, 2018)
Flywheel resistance training have in recent years become increasingly popular among athletes and coaches globally due to the advantages it provides over traditional strength training with weights. Exxentric, a company developing flywheel-based equipment for strength training and was looking to further increase the number of exercises that could be performed with their devices. Primarily, seated strength row exercises had been identified as a gap and there was a desire to develop an add-on product to extend their kBox device platform. To see if Exxentric could strengthen their business with an add-on for seated strength row, the thesis aimed to investigate the usefulness of such an add-on product. This was done through a usercentered design approach constructing a prototype and by developing a set of product design guidelines to be implemented on the prototype concept. The research for the user-centered design included market analyses, site observations and eight semi-structured interviews. Research data was analysed for three rounds to gain insights, ultimately generating five main themes to consider and evaluate against during the construction process. The main themes were adjustability, stability, durability, manageability and performance. With the themes in mind, the construction process was carried out for the add-on with focus on designing a seat, foot support, height setting, beam, leg and an interface towards the kBox. The final concept for the add-on measured 2218 mm long and 593 mm high when assembled. In addition to providing better possibilities for seated strength rows than any existing device within the product line, it also allowed for an additional four exercises to be performed with it.